Using high speed visualization to identify variations in the formation and distribution of plasmonic microbubbles - Mohammad Amer Allaf; Koji Okamoto; Takuto Owa (AIP Advances)
Plasmonic heating of gold nanoparticles (GNPs) using pulsed lasers (PLs) enables microbubble generation for imaging, diagnostics, and microfluidics. However, aggregation and photomodification cause inconsistencies (variations) in microbubble formation and distribution, particularly in pool-like environments where GNPs undergo aggregation and photomodification. This study experimentally investigates microbubble generation by heating GNPs (532 nm, nanoseconds PL) of various sizes and concentrations, using high-speed imaging (20 kfps). Results show unpredictable variations in bubble formation area (BFA), even under similar energy absorption. Large individual microbubbles were observed at relatively low energy absorption, primarily due to aggregation. Boiling on the transparent surface occurred in multiple tests, a phenomenon linked to optical pulling forces that deposited GNPs on the surface. This produced well-defined semi-circular bubbles (∼600 μm) within 50 μs. MB formation was more concentrated near the backward facing surface than along the laser beam, highlighting the role of optical pulling. Dissolved gas release influenced microbubble growth, particularly in samples prone to aggregation. In addition, prior laser pulses impacted BFA through photomodification and aggregation, sometimes reducing BFA despite higher energy absorption. This study provides new insights into the factors influencing microbubble formation and distribution in the plasmonic heating of GNPs. Understanding these mechanisms can help improve the reliability and efficiency of photothermal applications, enabling better control over plasmonic bubble generation for various scientific and technological advancements.